Analysis of the spatially distributed performance degradation of a polymer electrolyte membrane fuel cell stack - Cho, Min Kyung; Lee, Dae-Nyung; Kim, Yi-Young; Han, Jonghee; Kim, Hyoung-Juhn; Cho, Eunae; Lim, Tae-Hoon; Henkensmeier, Dirk; Yoo, Sung Jong; Sung, Yung-Eun; Park, Sehkyu; Jang, Jong Hyun (Pergamon Press Ltd., 2014)
Herein we report the spatially uneven degradation of a polymer electrolyte membrane fuel cell (PEMFC) stack operated under load variation. Fifteen sub-membrane electrode assemblies (sub-MEAs) at various cell positions and various points within each cell were obtained from the original MEAs employed in the fuel cell stack. Polarization curves and the voltammetric charge of these MEAs were measured in order to correlate localized performances with the redistributed electrochemically active surface on Pt using the polarization technique and cyclic voltammetry. Several ex situ characterizations including electron probe microanalysis, environmental scanning electron microscopy, and X-ray diffraction were also performed to find evidence, supporting the inhomogeneous degradation of the fuel cell stack. Possible routes and processes for the non-uniform stack degradation during the PEMFC stack operation will also be discussed. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.